Study of serum sodium and potassium concentration in cataract patients - Deokar, Smita A.; Rai, Pooja S.; Ingale, Pramod W.; Rai, Anita B.; Bakshi, Amruta A. (International Journal of Research in Medical Sciences, 2017)
Background: The present study was aimed to study alterations in levels of sodium and potassium in age-related cataract patients. Methods: 50 senile cataract patients in age group of 50 to 80 years and 50 control group were included for the study. Serum sodium and potassium levels were determined by flame photometry. Results: Significant (<0.0001) increased levels of plasma Na+ in cataract patients (145.06 ± 5.84mEq/lit) were found as compared with controls (141.18 ± 2.67mEq/lit). While Plasma K+ the conc. in cataract patients (4.18 ± 0.34mEq/lit) was not significantly (P = 0.002) increased when compared with controls (4.13 ± 0.32mEq/lit). Conclusion: Na, K-ATPase is responsible for maintaining the correct concentrations of sodium and potassium in lens cells. In ageing, lens fibers undergoes oxidation, and glycation may decrease Na, K-ATPase activity. The asymmetrical distribution of Na, K-ATPase activity in the epithelium and fibers may contribute to ionic currents that flow in and around the lens. So, abnormal elevation of lens sodium can be used as a marker in the opacification of the lens cortex in age-related human cataract.